Mind, Brain, and Language : Multidisciplinary Perspectives. - Banich, Marie T., 1957- (Taylor & Francis, 2003)
Much of the groundbreaking work in many fields is now occurring at the intersection of traditional academic disciplines. This development is well demonstrated in this important and unique volume, which offers a multidisciplinary view of current findings and cutting-edge issues involving the relationship between mind, brain, and language. Marie T. Banich and Molly Mack have edited a collection of 11 invited chapters from top researchers (and have contributed two of their own chapters) to create a volume organized around five major topics--language emergence, influence, and development; models o.